3d–4f Metallacrown complexes with a new sandwich core: synthesis, structures and single molecule magnet behavior. (11th August 2020) - Chang, Wen-Wen; Yang, Hua; Tian, Hai-Quan; Li, Da-Cheng; Dou, Jian-Min
Abstract : Two heterometallic metallacrown complexes, [Er{Cu4 (butyrat)4 }2 ]·Cl3 ·MeOH·26H2 O (1 ) and [Yb{Cu4 (butyrat)4 }2 ]·Cl3 ·MeOH·26H2 O (2 ) (H2 butyrat = 3-aminobutyric hydroxamic acid), have been reported. Abstract : Two heterometallic metallacrown complexes, [Er{Cu4 (butyrat)4 }2 ]·Cl3 ·MeOH·26H2 O (1 ) and [Yb{Cu4 (butyrat)4 }2 ]·Cl3 ·MeOH·26H2 O (2 ) (H2 butyrat = 3-aminobutyric hydroxamic acid), have been reported. X-ray crystallographic analysis reveals that the two complexes displayed nested-sandwich configurations with two 12-MC-4 metallacrown units capping Ln III in the centre. Magnetic studies revealed that 1–2 undergo antiferromagnetic coupling interaction. Magnetic measurements show that complex 2 displays frequency-dependent signals at a dc field of 1000 Oe, indicating field-induced single-molecule magnet behavior.